Export Performance and External Competitiveness in the former Yugoslav Republic of Macedonia - Gutierrez, Eva (IMF Working Papers; Working Paper ;, 2006)
This paper reviews a broad set of indicators of competitiveness in the Macedonian economy and estimates the equilibrium real effective exchange rate (REER) using different methodologies. Although the REER is broadly in equilibrium at present, structural factors are found to hamper competitiveness. While a more competitive exchange rate might improve short-term export performance, sustained improvements require enhanced productivity and resource reallocation to more dynamic sectors, which depends on reforms to improve the business environment.